Integral Projection Models and Sustainable Forest Management of Agave inaequidens in Western Mexico - Torres-García, Ignacio; León-Jacinto, Alejandro; Vega, Ernesto; Moreno-Calles, Ana Isabel; Casas, Alejandro (Frontiers in Plant Science, 2020)
In México, at least 37 Agave species are extracted from wild populations for producing distilled spirits, severely affecting their sexual reproduction. An increasing demand on agaves spirits is determining a massive pressure on wild populations, most of them lacking adequate management. But in addition, the dynamics of agave populations may be affected by natural processes like oscillation of rain regimes, which affects the recruitment of agave seedlings, or scarcity of pollinators that may affect seed production and general population dynamics. We studied the demography of wild populations of Agave inaequidens to analyse critical conditions for populations recovery, modelling the effects rainfall trends on the demographic performance of this species, and exploring response of populations to hypothetical extraction regimes and reforestation efforts. Our study was performed in four well-conserved wild populations of western Mexico, each population sampled in plots of about one hectare composed by 10 subplots 50 x 5 m (2500 m2), where populations were monitored yearly between 2011 and 2013, measuring plant size, reproductive individuals and fecundity. Data were analysed through integral projection models by using the IPMpack for R, performing prospective analyses. We in addition constructed stochastic models to explore the possible influence of rainfall variation on species demography, using data for the drier and wetter years of the study period. Population growth varied from λ=1.003 to λ=0.899 among populations and years, and exceptionally λ=0.559 after a burning event. Low rainfall decreases λ values, indicating especial limitations to harvesting agaves during dry years whose frequency most probably will increase. In general, extraction rates from 10% to 30% of mature individuals are viable to maintain λ above 1, and these rates may be high if new plants are introduced in populations. Depending on levels of extraction, our models suggest that it is necessary to carry out actions of reforestation, and in situ management according to the trends found in each site. This is one indispensable condition to maintain λ close to or greater than 1. Sustainable extraction of wild agaves is possible, but together with ecological criteria, strict regulations and social organization are needed.